ABUNDANCE AND DIVERSITY OF ECHINODERM IN PARI ISLAND, SERIBU ISLANDS - Supono Supono; Ucu Yanu Arbi (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2012)
Pari Island is one of the island in the Seribu Islands region. Abundance of echinoderms in Pari Island waters has been observed since 1969. In this research, data of echinoderms was collected on March 2011 applying quadratic transect method 1 x 1 m2, as well as freely collection methods using snorkel and scuba equipment. Thirteen individuals of echinoderms were collected during the study, one species (Archaster typicus) was found by quadratic transect method and 12 species of echinoderms by freely collection methods. The density of starfish Archaster typicus at the sites was between 2.1 to 4.3 individual/m2.Keywords: Echinodermata, distribution, abundance, density, Pari Island, Seribu Islands